1984
DOI: 10.1111/j.1399-3054.1984.tb06082.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and ageing of membranes from etioplasts of Avena sativa

Abstract: A growth period from day 4 to day 11 after sowing of dark‐grown oat seedlings (Avena sativa L. cv. Flämingskrone) was studied. Etioplasts were prepared from various stages. By means of one and two dimensional gel eletrophoresis developmental changes in the polypeptide pattern of the prolamellar body‐prothylakoid complex of etioplasts were studied. Polypeptides were described by their molecular weights and pI values after isoelectric focusing. The polypeptide map changes continuously with age, with the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Again, the predicted reductase sequence (Fig. 10) with its relatively high bl-sic amino acid content (Arg and Lys accounting for 120%) makes it possible to comprehend the high pI values (8.2-8.5) reported for the reductase (Ikeuchi & Marakami, 1982;Bergweiler et al, 1983). This basic property might also be considered in assigning a role for the reductase in the etioplast membrane.…”
Section: Discussionmentioning
confidence: 94%
“…Again, the predicted reductase sequence (Fig. 10) with its relatively high bl-sic amino acid content (Arg and Lys accounting for 120%) makes it possible to comprehend the high pI values (8.2-8.5) reported for the reductase (Ikeuchi & Marakami, 1982;Bergweiler et al, 1983). This basic property might also be considered in assigning a role for the reductase in the etioplast membrane.…”
Section: Discussionmentioning
confidence: 94%
“…The etioplasts themselves may well be such a target. Indeed, Bergweiler et al, (1984), using isolated etioplasts and protein analysis, showed that, in the case of oat leaves, etioplast proteins were degraded during prolonged etiolation. In the present work, the step by step description of cotj'ledon energy metabolism has related degradation processes during etiolation with carbohydrate starvation, rather than with Intrinsic ageing or senescence of plastids.…”
Section: Discussionmentioning
confidence: 99%
“…There is no distinct border between them in situ. Together they constitute a dynamic system where the relative amount of the two structures depends on plant species, age and growth conditions of the plant (Lutz 1981, Bergweiler et al 1984, Frances et al 1992. The lipid to protein ratio is higher in PLBs than in PTs, and so is the ratio of monogalactosyldiacylglycerol (MGDG) to digalactosyldiacylglycerol (DGDG; Sandelius 1984, Protoschill-Krebs andKesselmeier 1988).…”
Section: Prolamellar Bodies and Prothylakoidsmentioning
confidence: 98%
“…Two membrane structures can be seen in electron micrographs of etioplasts, the prolamellar bodies (PLBs), which are composed of highly regular networks of tubular membranes, and the lamellar-like prothylakoids (PTs). During continuous irradiation the PLBs will disappear and normal thylakoids will form in 24 to 96 h (Boardman and Anderson 1978), if the plants are not too old (Bergweiler et al 1984, Rascio et al 1984). There are a number of excellent reviews within the field (e.g.…”
Section: Introductionmentioning
confidence: 96%